Projecting Emissions Baselines for National Climate Policy Options for Guidance to Improve Transparency - Clapp, Christa (OECD/IEA Climate Change Expert Group Papers, 2012)
Greenhouse gas (GHG) emissions baselines are reference emissions levels. This paper focuses on projected forward-looking baselines that can be used both to inform national climate policy and to set goals that are defined relative to a business-as-usual (BaU) scenario. As some developing countries have defined national mitigation goals for 2020 in this way, the underlying assumptions and methodologies used in setting these emissions baselines are relevant for assessing the magnitude of both the country's expected total emissions reductions and the global aggregate emissions mitigation effort. Currently, there is limited international guidance available on setting national GHG baselines. The resulting variance and lack of transparency makes it difficult to understand emissions pledges defined as relative to BaU, and difficult to compare emissions scenarios across countries. Moving towards international guidance on setting baselines could improve transparency, clarity and comparability, while still allowing countries to maintain diversity in approaches. This paper discusses good practice and presents options for how guidance might be developed for key elements of baseline setting. The options are presented as "tiers" that move from less detailed to more detailed guidance. The first tier describes guidance that would leave maximum flexibility for individual countries, whilst encouraging transparency. The second tier offers more detailed guidance for countries with greater domestic resources and capabilities. Countries could adhere to the tiers according to their capabilities, although they would be encouraged to follow the more detailed approach. The proposed tiers represent different levels of detail, rather than accuracy or data quality. More detailed guidance does not necessarily lead to "better" baselines, though it may help to improve understanding of different baselines